Epstein-Barr virus nuclear protein 3C modulates transcription through interaction with the sequence-specific DNA-binding protein J kappa. - Robertson, E S (1995)
The Epstein-Barr virus (EBV) nuclear protein 3C (EBNA 3C) is essential for EBV-mediated transformation of primary B lymphocytes, is turned on by EBNA 2, and regulates transcription of some of the viral and cellular genes which are regulated by EBNA 2. EBNA 2 is targeted to response elements by binding to the DNA sequence-specific, transcriptional repressor protein J kappa. We now show that EBNA 3C also binds to J kappa. EBNA 3C causes J kappa to not bind DNA or EBNA 2. J kappa DNA binding activity in EBV-transformed lymphoblastoid cells is consequently reduced. More than 10% of the EBNA 3C coimmunoprecipitated with J kappa from extracts of non-EBV-infected B lymphoblasts that had been stably converted to EBNA 3C expression. EBNA 3C in nuclear extracts from these cells (or in vitro-translated EBNA 3C) prevented J kappa from interacting with a high-affinity DNA binding site. Under conditions of transient overexpression in B lymphoblasts, EBNA 2 and EBNA 3C associated with J kappa and less EBNA 2 associated with J kappa when EBNA 3C was coexpressed in the same cell. EBNA 3C had no effect on the activity of a -512/+40 LMP1 promoter-CAT reporter construct that has two upstream J kappa sites, but it did inhibit EBNA 2 transactivation of this promoter. These data are compatible with a role for EBNA 3C as a "feedback" down modulator of EBNA 2-mediated transactivation. EBNA 3C could, in theory, also activate transcription by inhibiting the interaction of the J kappa repressor with its cognate DNA. The interaction of two viral transcriptional regulators with the same cell protein may reflect an unusually high level of complexity or stringency in target gene regulation.